Kepentingan Ideologis Negara dan Nahdlatul Ulama dalam Pembubaran Hizbut Tahrir Indonesia - Fauzi, Ahmad Irfan; Kosandi, Meidi (Universitas Islam Malang, 2022)
This article discussed the contestation of ideological interests between the state, Hizbut Tahrir Indonesia (HTI), and Nahdlatul Ulama (NU) in the case of the disbandment of HTI in 2017. The disbandment of HTI explained the existence of pro and contra groups and the attraction of ideological interests. This research was qualitative research with observation and interview methods. The research results proved that there were conflicting and conflicting interests between the interests of the state, HTI, and NU. The state interests were the interests of the Pancasila ideology and public security. NU rejected the caliphate because it was interested in defending the